Cerebral microemboli detected by transcranial doppler in patients treated with extracorporeal membrane oxygenation. Issue 7 (24th April 2016) - Marinoni, M.; Migliaccio, M. L.; Trapani, S.; Bonizzoli, M.; Gucci, L.; Cianchi, G.; Gallerini, A.; Tadini Buoninsegni, L.; Cramaro, A.; Valente, S.; Chiostri, M.; Peris, A.
Abstract : Introduction: Cerebrovascular complications rate in patients treated with extracorporeal membrane oxygenation (ECMO) is about 7%. Ischemic stroke may be caused by solid or gaseous microemboli due to thrombosis within the circuit or cannula. Transcranial Doppler (TCD) is the only method able to detect microembolic signals (MES) in real time. The objective of this study was to detect possible MES by TCD in patients treated with veno‐venous (VV) and veno‐arterial (VA) ECMO and to test for a relation between the number of MES and the 6‐month clinical outcome of these patients. Methods: This is a monocentric observational prospective study in patients consecutively admitted and treated with ECMO at our regional ECMO referral center in 18 months. TCD detection of MES was performed in patients upon initiation of treatment and then repeated during treatment. Results: Two hundred and forty‐eight TCD monitoring were performed in 42 VV and 11 VA ECMO patients. MES were detected in 26.2% of VV ECMO patients and in 81.8% of VA ECMO patients ( P < 0.001). In both subgroups of patients, no correlation was found between MES detection and extracorporeal flow velocities or aPTT values. In VA ECMO patients, an inverse correlation between left ventricular ejection fraction and MES grading was found ( P = 0.037). In both groups, no clinical neurological impairments correlated to MES detection were found at 6 months follow‐up. Conclusions: MES were found in both ECMO configurations; independently from their pathophysiology, MES do not seem to influence clinical outcome. Multicenter studies are still required with more extensive cases to confirm these results.